STUDYING OF COMORBID PATHOLOGY AT THE 2 TYPES DIABETES AS THE COMPLICATION OF THE METABOLIC SYNDROME - S. P. Melikhova; V. I. Shevcova; A. A. Zujkova; Yu. A. Kotova (Архивъ внутренней медицины)
Purpose. To define features of comorbid pathology at patients with a 2 types diabetes, to estimate a possibility of use of indexes of a comorbid pathology in the management of these patients. Materials and methods. Patients with a 2 types diabetes participated in a research. The retrospective analysis of medical records with calculation of indexes of a comorbid pathology for the systems CIRS, Kaplan-Feinstein, Charlson was made. Taking into account the received indexes at patients prognostic indicators of percentage risk of lethality within the next year and 10-year survival were defined. Correlation interrelations between laboratory indicators of components of a metabolic syndrome and values of indexes of a a comorbid pathology are defined. Results. It was defined that in structure of comorbid pathology at the chosen patients diseases of cardiovascular, nervous and genitourinary systems prevail. Besides the specified systems, at women specific gravity of pathology of endocrine system is big. With age the tendency to prevalence of comorbid pathology of the specified systems remains and also the augmentation of average score of indexes of a comorbid pathology on all systems, deterioration in prognostic indicators is taped. Statistically significant direct link between indexes of a comorbid pathology and separate components of a metabolic syndrome, an experience of a disease of patients is also taped.